2022
DOI: 10.3390/dj10090173
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Platelet Rich Plasma (PRGF) Preserves Genomic Stability of Gingival Fibroblasts and Alveolar Osteoblasts after Long-Term Cell Culture

Abstract: Plasma rich in growth factors (PRGF) has several applications in dentistry that may require repeated applications of PRGF. Furthermore, it has been used for ex vivo expansion of human origin cells for their clinical application. One of the most relevant issues in these applications is to guarantee the genetic stability of cells. In this study, the chromosomal stability of gingival fibroblasts and alveolar osteoblasts after long-term culture was evaluated. Cells were expanded with PRGF or foetal bovine serum (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Osteoblast activity is regulated by the secretion of calcium and phosphate ions into the adjacent tissue. Elevated concentrations of extracellular calcium impede the formation of osteoclasts while stimulating DNA synthesis and chemotaxis in osteoblastic cells [5,30]. In the interim, it has been observed that CHA induces an upregulation in the expression of transforming growth factor-β1 (TGF-β1) and bone morphogenic protein-2 (BMP-2), both of which play a significant role in the process of osteoblastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblast activity is regulated by the secretion of calcium and phosphate ions into the adjacent tissue. Elevated concentrations of extracellular calcium impede the formation of osteoclasts while stimulating DNA synthesis and chemotaxis in osteoblastic cells [5,30]. In the interim, it has been observed that CHA induces an upregulation in the expression of transforming growth factor-β1 (TGF-β1) and bone morphogenic protein-2 (BMP-2), both of which play a significant role in the process of osteoblastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the CGH array (Genomic Hybridization Assay) to consider chromosomal stability did not reveal genetic instability. The autologous PRGF technology, according to Anitua et al, Preserves the genomic stability of the cells and represents a valid alternative to the FBS culture medium and therefore a good supplement for cell therapy 49 .…”
Section: Prp Vs Prgfmentioning
confidence: 99%